EFEITO DO THIOBACILLUS THIOOXIDANS NA CORROSÃO DO AÇO 430 - Anunziato, Priscila Aparecida (2008)
It is known that metals immersed in aqueous systems are easily colonized by microorganisms. As a result of colonization of microorganisms in metal, the metal surface becomes covered with a biofilm. These microbial Biofilms are very complex due to their different microbial populations, usually in the form polymer separated by canals and empty spaces, which develop in virtually all the metal surface. The most serious accidents occur in biocorrosion of anaerobic environments, as in soil and thick with biofilms. The microbiological corrosion is a big problem of today , given the variety of environments that may have colonies of bacteria, many equipment that can suffer this type of corrosion. The oil and alcohol industries are the biggest sufferers with this type of oxidation. The objective of this work is the influence of Thiobacillus Thiooxidans (TT) in the corrosion of 430 stainless steel (SS) in H2SO4 1 mol L-1. In this study of the techniques were employed: measures of mass loss, cyclic potentiodynamic polarization (CPP) and potentiostatic anodic polarization (PAP), electrochemical impedance spectroscopy (EIS), optical (OM) and scanning electron microscopy (SEM). The results showed that gravity in 180 minutes of immersion of steel in the solution containing TT there is the formation of biofilms, which initially blocks the corrosion of the metal. The PAP has shown that the TT works catalysing the reaction of oxidation of 430 SS in this solution, similar results were obtained by the EIS. The implementation of the CPP in the region passive steel 430, in this solution, inhibit the generation of biofilms on the surface, which was confirmed by SEM.